The Influence of Global Cultural Infiltration on the Sasak Traditional Marriage System in Lombok Island - Muhamad Alfin Tarmizi; Siti Sanisah; Sukuryadi Sukuryadi; Ravinesh Rohit Prasad; Junaidin Junaidin; Mas’ad Mas’ad (JURNAL GEOGRAFI, 2024)
The essence and existence of culture in its process will gradually change due to various factors, such as the infiltration of global culture. This quantitative study aims to determine the effect of global cultural infiltration on the traditional Sasak marriage system in Lombok Island. The research was conducted in Montong Gamang Village, Kopang District, Central Lombok Regency, with 50 respondents determined by purposive sampling. The research data were obtained through a questionnaire analyzed using the Product Moment Correlation formula. The analysis results show a correlation coefficient (0.639) greater than the value of r-Product Moment (0.279) at a significance level of 5%. This means that global cultural infiltration has a significant effect on the traditional Sasak marriage system in Lombok Island. It is suggested that the tribe can wisely select and accept the foreign culture, be aware of negative influences, and maintain local cultural values. Keywords: Cultural Infiltration; Marriage System; Sasak Tribe Custom